Advances in thermal and non-thermal food preservation - Tewari, Gaurav; Juneja, Vijay K., 1956- (Blackwell Publishing, 2007)
"Advances in Thermal and Non-Thermal Food Preservation provides current, definitive and factual material written by experts on different thermal and non-thermal food preservation technologies. Emphasizing inactivation of microorganisms through the application of traditional as well as newer and novel techniques and their combinations, the book's chapters cover:.:.; thermal food preservation techniques (e.g., retorting, UHT and aseptic processing), .; minimal thermal processing (e.g., sous-vide processing), and.; non-thermal food preservation techniques (e.g., high pressure processing and pulsed."-- Resumé vydavatele
Keywords: potravinářská technologie; konzervování potravin; potravinářská mikrobiologie; food technology; food preservation; food microbiology; kolektivní monografie; elektronické knihy; collective monographs; electronic books